The Role of Governance and Technology in Shaping Equitable Fiscal Policy - Pradono, Nuswantoro Setyadi (Moneta : Journal of Economics and Finance, 2024)
This review addresses the gap in fiscal sustainability studies by analyzing how governance and technology jointly shape equitable fiscal outcomes across regions. Unlike prior reviews that remain descriptive, this paper integrates findings into a conceptual lens that highlights digital inclusion and participatory governance as underexplored drivers of fiscal resilience. By synthesizing evidence from diverse contexts, the study provides a novel perspective on bridging institutional and technological divides in fiscal systems. These measures are essential to achieving sustainable fiscal outcomes and reducing disparities in access and service delivery across global contexts.